Evaluation of the Strategic Performance of the State Board of Antiquities and Heritage/Case Study - Fakher Abd AL- Hassan, Rasha; Sakr Maktouf, Hanadi (Journal of Economics and Administrative Sciences, 2022)
This research aims to the possibility of evaluating the strategic performance of the State Board for Antiquities and Heritage (SBAH) using a balanced scorecard of four criteria (Financial, Customers, Internal Processes, and Learning and Growth). The main challenge was that the State Board use traditional evaluation in measuring employee performance, activities, and projects. Case study and field interviews methodology has been adopted in this research with a sample consisting of the Chairman of the State Board, 6 General Managers, and 7 Department Managers who are involved in evaluating the strategic performance and deciding the suitable answers on the checklists to analyze it according to the 7-points Likert scale. Data analysis results have been extracted using statistically weighted averages via Excel 365, and one of the main outcomes of this research is that the process of evaluating the strategic performance of the State Board for Antiquities and Heritage is of great importance for its impact on the State’s activities for it has high flexibility to adjust its goals according to the environment that controls the State. Paper type Categories your paper under one of these classifications: A case study.